2019
DOI: 10.3892/etm.2019.8023
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and prognostic analysis of 49�cases with crescentic glomerulonephritis

Abstract: Rapidly progressive glomerulonephritis (RPGN), characterized by rapid kidney dysfunction caused by aggressive glomerulonephritis, is usually associated with crescentic glomerulonephritis (CrGN). In the present study, the data from patients with CrGN were retrospectively analyzed at a tertiary medical center in China with the aim of investigating the clinicopathological features and the association of the type of CrGN with the prognosis. The renal biopsies of 49 patients diagnosed with CrGN were obtained betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
18
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 29 publications
9
18
4
1
Order By: Relevance
“…However, we found no cases of low C4 levels in type I and III Cr.GN, highlighting that the alternate complement pathway has a role in the pathogenesis of these GNs. Our observed rates of ANCA seropositivity in type III Cr.GN are much lower than those reported in other studies 2 , 15 . An earlier study from India also reported similar rates of ANCA seropositivity 16 .…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…However, we found no cases of low C4 levels in type I and III Cr.GN, highlighting that the alternate complement pathway has a role in the pathogenesis of these GNs. Our observed rates of ANCA seropositivity in type III Cr.GN are much lower than those reported in other studies 2 , 15 . An earlier study from India also reported similar rates of ANCA seropositivity 16 .…”
Section: Discussioncontrasting
confidence: 76%
“…However, in this study, more than half of the patients with type II and III Cr.GN also presented with severe renal failure, highlighting the dramatic presentation in this patient population. These rates are much higher than previously reported 2,15 .…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Some of the abovementioned features of APN-induced severe AKI seem to resemble other causes of AKI, including AIN, acute tubular necrosis (ATN) and rapidly progressive glomerulonephritis (RPGN). All of these conditions can cause AKI with bilateral kidney enlargement ( 27 , 28 ). The common clinical manifestations of AIN are nonspecific, including asthenia, anorexia, nausea and vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…These rates are much higher than previously reported. 2,15 Serum complement C3 levels have been shown to be low in type I and type III Cr.GN in addition to type II Cr.GN. The same was confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%